Synthesis of Poly Acrylic Acid (PAA) Modified Silver Nanoparticles, Using Trisodium Citrate for Heavy Metal Detection - Yussi Pratiwi; Adelia Widyaresti; Tritiyatma Hadinugrahaningsih; Elsa Vera Nanda; Devi Nur Anisa (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
Therefore, this project was to prepare and characterize silver nanoparticles (AgNPs) and study their application for colorimetric detection of heavy metal ions. AgNPs are synthesized by a bottom-up method in which AgNO3 serves as the precursor, which is then reduced using trisodium citrate and stabilized by 1 vol.% polyacrylic acid (PAA). Trisodium citrate facilitates the reduction of Ag+ ions due to its negatively charged carboxylic groups, whereas PAA enhances stability and selectivity. Under the best reaction parameters condition, AgNPs produced brown-yellow colloids with a Surface Plasmon Resonance (SPR) peak of 403 nm. A particle size analysis showed an average particle diameter of 29.9 nm, with a standard deviation σ of 0.482. Fourier Transform Infrared Spectroscopy (FTIR) analysis confirmed that hydroxyl groups -OH and carbonyl groups C=O play a role in reducing Ag+ ions. Because they are highly active, AgNPs can respond to Hg2+ in tests, marking the color change from brown-yellow to transparent white within about one minute. Methods testing for validation of linearity revealed an R2 = 0.9985, and a LOD and LOQ are ca. 0.074 ppm and 0.224 ppm, respectively. At 700 ppm Hg2+, the selectivity was good. These results demonstrate that AgNPs are sensitive and efficient sensors of Hg2+ ions and indicate how to find promising new ways to detect heavy metals in environmental monitoring.